Adding dried distillers grains to swine diets affects feed preference - Hastad, C.W.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Three studies were conducted to evaluate the effects of dried distillers grains with solubles (DDGS) on feed intake in growing pigs. In all experiments, pigs were housed in 10.5 × 10.3 ft pens with four 1-hole feeders in each pen to allow pigs to choose from four dietary treatments. In Experiment 1, we evaluated the influence of DDGS drying method on palatability of DDGS. Diets were a control corn soybean-meal diet or a corn soybean-meal diet with 30% DDGS from one of two drying techniques (plant dried, hand dried, or not dried). Overall, ADFI was less (P<0.05) for all DDGS drying methods than for the cornsoybean control. For Experiment 2, we compared the influence of DDGS grain source on feed intake. We compared differences between a corn-soybean meal diet and cornsoybean meal diets with 30% DDGS from two corn facilities or one milo facility. Overall, adding 30% DDGS from all sources reduced (P<0.05) ADFI below that of corn-soybean meal diets. In Experiment 3, we used gas chromatography/mass spectrometry (GC/MS) to identify compounds found in DDGS sources from Experiment 2 to determine if any specific compounds are responsible for negative effects on feed intake. We added Furfural, γ-Butyrolactone, and Phenyl ethyl alcohol to corn-soybean meal diets at twice the concentration found in diet with 30% DDGS. We fed a control corn soybean-meal diet or corn soybean-meal with 20 ppm of each compound per ton of complete feed. The addition of each individual compound had no effect (P>0.55) on feed intake. These studies illustrate that pigs prefer corn-soybean diets to diets containing DDGS. The decrease in palatability seems to increase with increasing amounts of dried distiller grains. Although the nutrient content of DDGS make it an attractive ingredient for swine diets, palatability problems may affect pig performance, even when DDGS is included at low rates in the diet.
Swine research, 2005 is known as Swine day, 2005
Keywords: Swine; Pigs; Feed intake; DDGS